Sintesis bioplastik dari pati sagu dengan penambahan selulosa limbah kertas dan plasticizer gliserol–sorbitol - Wiza Ulfa Fibarzi; Rizka Nurlaila; Raudhatul Ulfa; Yohana Dian Putri; Suci Luthphia Masri; Vivi Febry Katanti (Jurnal Rekayasa Proses, 2026)
Bioplastics are natural-based plastics that can degrade in the environment, making them more eco- friendly. Paper waste contains cellulose with potential as a raw material for bioplastic production. This study aimed to analyze the properties of cellulose-based bioplastics derived from paper waste with the addition of sago starch and plasticizers. The manufacture of bioplastics used a variation treatment of cellulose additions of 1 gram, 2 grams, 3 grams, and without cellulose, and a plasticizer (glyserol + sorbitol) volume of 2 ml, 3 ml, 4 ml, and 5 ml. Characterization included swelling (water absorption), tensile strength, biodegradability, and thermal stability tests. Functional groups of the extracted cellulose were also examined. The extracted cellulose was characterized using FTIR and showed characteristic functional groups of cellulose, such as O–H, C–H, and C–O–C. Swelling tests showed that most bioplastic samples had values below 30 %, indicating good water resistance according to standard criteria (≤30 %). The lowest swelling was observed in samples without cellulose and with 5 mL plasticizer (15.78 %), while the highest occurred in samples with 3 g cellulose and 2 mL plasticizer (42.69 %). The best composition was obtained with 3 g cellulose and 5 mL plasticizer, giving optimal mechanical properties: tensile strength 4.08 MPa, Young’s modulus 74.85 MPa, and elongation 5.74 %. At this formulation, swelling was only 29.50 %, confirming good water resistance. Biodegradability testing also confirmed that all samples exhibited good decomposition ability in accordance with SNI 7188.7:2016 standards.Overall, the utilization of cellulose derived from paper waste combined with glycerol–sorbitol plasticizers successfully produces bioplastics with adequate mechanical properties, controlled water resistance, and high biodegradability. This formulation demonstrates strong potential as an environmentally friendly packaging material to replace conventional plastics.